TIMP-1 enhances Akt and BDNF signaling in neurons to reduce synaptic and cognitive deficits in 5xFAD mouse model of Alzheimer’s disease - Sukanya Sarkar; Kusumika Gharami; Ananya Mondal; Keerthana Padmanabhan; Ramesh Kumar Paidi; B. N. Srikumar; Subhas C. Biswas (Acta Neuropathologica Communications)
Abstract Glial-secreted molecules influence neuronal function in Alzheimer’s disease (AD), but their mechanisms of action are partially understood. Anti-inflammatory cytokine tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) is secreted by astrocytes early in response to amyloid-β and is suggested to have a neuroprotective function. We demonstrated that TIMP-1 levels are increased in 7-day-old 5xFAD versus wild-type mice but are drastically decreased from two months onwards. Administration of TIMP-1 protein in 5xFAD mice ameliorated AD-associated cognitive impairments. TIMP-1 regulated both neuronal apoptosis and autophagy by binding to CD63 receptors in an AD model. Synaptosomal and electrophysiological studies revealed that TIMP-1 reduces AD-related synaptic deficits, likely by promoting post-synaptic long-term potentiation in the hippocampus, independent of pre-synaptic activity. TIMP-1 induced brain-derived neurotrophic factor (BDNF) and BDNF-mediated post-synaptic signaling. These findings suggest that TIMP-1 functions as a multifunctional cytokine with protective and long-term benefits for neurons and may be a promising therapeutic candidate in AD.